Hubungan antara perilaku sedentari dengan status gizi pada pelajar - Therianto, Febrina Melly Chriesanty; Musa, Ester Candrawati; Langi, Fima Lanra Fredrik Gerarld (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Sedentary behavior, or a lack of movement, can have negative health consequences if allowed to persist over time. One impact of sedentary behavior is nutritional status. Teenagers who are sedentary are also at higher risk of obesity and non-communicable diseases (chronic illnesses). Purpose: To analyze the relationship between sedentary behavior and nutritional status. Method: This quantitative research used a cross-sectional approach. The population studied were students at State Senior High School 2 Tondano in July-September 2025. The sample used was 88 respondents selected through a total sampling technique. The instruments used were the Physical Activity Questionnaire of Adolescents (PAQ-A) questionnaire to observe physical activity and assess sedentary behavior of students in adolescence, and a height and weight measuring instrument to measure nutritional status. Results: The average physical activity questionnaire of adolescents (PAQ-A) score of students was quite low, with results around 1.80 with a standard deviation of 0.40. The average sample student had a body mass index (BMI) in the good category (mean 22.09 ± 5.14 kg/m2). However, 14 (16%) of the sample students were in the obese category (BMI/U Z score above +2 SD). The results of the bivariate analysis obtained a p value of 0.65 (p>0.05), meaning that H0 was accepted and the hypothesis was rejected. This indicates that there is no relationship between sedentary behavior and nutritional status in students. Conclusion: The association between sedentary behavior and nutritional status was not statistically significant, but the direction of the association suggests that lower physical activity may be associated with an increased risk of overnutrition. Suggestion: Further research with longitudinal designs and more objective measures of sedentary behavior is recommended to strengthen the causal evidence. Keywords: Nutritional Status; Sedentary Behavior; Students. Pendahuluan: Perilaku sedentari merupakan perilaku menetap atau kurang bergerak, perilaku ini memiliki dampak buruk untuk kesehatan jika dibiarkan dalam waktu yang lama. Salah satu dampak yang dapat dipengaruhi oleh perilaku sedentari yaitu status gizi. Remaja yang kurang bergerak juga dapat berisiko lebih tinggi mengalami kegemukan, hingga berisiko mengalami penyakit tidak menular (penyakit kronis). Tujuan: Untuk menganalisis hubungan antara perilaku sedentari dengan status gizi. Metode: Penelitian kuantitatif dengan pendekatan cross-sectional. Populasi yang diteliti adalah pelajar di SMA Negeri 2 Tondano pada bulan Juli-September 2025. Sampel yang digunakan sebanyak 88 responden yang dipilih melalui teknik total sampling. Instrumen yang digunakan yaitu kuesioner physical activity questionnaire of adolescents (PAQ-A) untuk melihat aktivitas fisik dan menilai perilaku sedentari pelajar diusia remaja, alat ukur tinggi badan dan berat badan untuk mengukur status gizi. Hasil: Rata-rata skor PAQ-A pelajar cukup rendah dengan hasil di sekitar 1.80 dengan standar deviasi 0.40. Rata-rata pelajar sampel memiliki indeks massa tubuh (IMT) dalam kategori baik (mean 22.09 ± 5.14 kg/m2). Namun, sebanyak 14 responden (16%) telah berada di kategori obese (skor Z IMT/U di atas +2 SD). Hasil analisis bivariat diperoleh p value sebesar 0.65 (p>0.05), artinya H0 diterima, maka hipotesis ditolak. Hal ini menunjukkan tidak terdapat hubungan perilaku sedentaridengan status gizi pada pelajar. Simpulan: Hubungan antara perilaku sedentari dan status gizi tidak signifikan secara statistik, namun arah hubungan menunjukkan bahwa aktivitas fisik yang lebih rendah mungkin berkaitan dengan peningkatan risiko gizi lebih. Saran: Penelitian lanjutan dengan desain longitudinal dan pengukuran perilaku sedentari yang lebih objektif disarankan untuk memperkuat bukti kausal. Kata Kunci: Pelajar; Perilaku Sedentari; Status Gizi.